Dietary patterns associated with the risk of type 2 diabetes in women with and without a history of gestational diabetes mellitus: a pilot study - Hasbullah, Farah Yasmin; Mohd Yusof, Barakatun Nisak; Abdul Ghani, Rohana; Appannah, Geeta; Mat Daud, Zulfitri ’Azuan; Abas, Faridah (Nutrition Society of Malaysia, 2023)
Introduction: There is limited evidence on dietary patterns and the risk of type 2 diabetes (T2D) in women with a history of gestational diabetes mellitus (GDM) compared to their non-GDM counterparts, especially in the Asian population. The pilot study investigated dietary patterns in women with a history of GDM (HGDM) and without a history of GDM (non-HGDM), and the association with T2D risk. Methods: This comparative cross-sectional study involved 64 women (32 HGDM, 32 non-HGDM). Food intake was assessed using a validated food frequency questionnaire. Principal component analysis derived the dietary patterns. T2D risk score was determined using the Finnish Diabetes Risk Score tool. Results: HGDM group had significantly higher proportion of first-degree family history of diabetes; higher risk of T2D and better diabetes knowledge; lower gestational weight gain and postpartum weight retention; and consumed more fast food than nonHGDM. ˜Rice-noodle-pasta-meat dietary pattern was significantly associated with increased T2D risk after adjusting for age (²=0.272, p=0.032). ˜Bread-cereals-fast food-meat dietary pattern was positively and significantly associated with T2D risk after adjusting for confounders, including age, education level, family history of diabetes, diabetes knowledge score, gestational weight gain, and postpartum weight retention (²=0.251, p=0.012). Conclusion: Dietary patterns high in bread, cereals and cereal products, fast food and meat, as well as rice, noodle, pasta and meat were associated with an elevated T2D risk. A more extensive study is warranted to establish the association between dietary patterns and risk of T2D, focusing on women with a history of GDM.